Taxonomic classification of butterflies in Lake Imelda, Ormoc, Leyte - Fran, James; Yong, Armelina; de los Reyes, Cesar (Tacloban City James Fran [and] Armelina Yong, 1987)
A Taxonomic Classification of Butterflies was conducted in Lake Imelda, Ormoc, Leyte from November 1986 to February 1987.
Ten species and fifteen subspecies of butterflies belonging to seven families and twenty genera were studied and identified easily on wings venation together with other external visible characteristic features. All the species of butterfly collected were classified under families: Papilionidae, Satyridae, Nymphalidae, Damidae, Lycaenidae, Pieridae and Amathusiidae.
Undergraduate thesis (B.S. in Biology)--University of the Philippines, Tacloban.
Keywords: Butterflies -- Taxonomic classification -- Lake Imelda, Ormoc, Leyte; Science and Technology